Electrode assembly, battery and electric equipment

By designing the first active substance with a core-shell structure and the second active substance containing doped elements, combined with the arrangement of the protective layer, the problem of lithium-ion batteries being excited under high capacity is solved, and the battery life is extended and the energy density is maintained.

CN119905682AActive Publication Date: 2025-04-29XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510095643.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-29
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

In the pursuit of high capacity, lithium-ion batteries lead to deterioration in material processing and electrical properties, and lithium-ion excision phenomenon, affecting the service life of the battery.

Method used

An electrode assembly is designed, wherein the positive electrode sheet includes a current collector layer, a first material layer and a second material layer. The first material layer is composed of a first sub-layer and a second sub-layer. The first active substance in the first sub-layer has a core-shell structure. The active substance in the second sub-layer and the second material layer contains a doping element. By adjusting the mass content of the doping element and the setting of the protective layer, the diffusion ability of the lithium ions is controlled.

Benefits of technology

It effectively slows down the lithium evolution phenomenon on the surface of the negative electrode sheet, extends the service life of the battery, and maintains the high energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905682A_ABST
    Figure CN119905682A_ABST
Patent Text Reader

Abstract

The invention relates to an electrode assembly, a battery and electric equipment. The electrode assembly is of a winding structure and has a central axis, the electrode assembly comprises a positive pole piece, the positive pole piece comprises a current collector layer, a first material layer and a second material layer, the first material layer is arranged on the side, facing the central axis, of the current collector layer, the first material layer comprises a first sub-layer and a second sub-layer, the first sub-layer is closer to the central axis than the second sub-layer, and the second sub-layer is closer to the central axis than the first sub-layer. The first sub-layer comprises a first active substance, the first active substance comprises an inner core and a protective layer, the inner core comprises lithium iron phosphate and a first doping element, the second sub-layer comprises a second active substance, and the second active substance comprises lithium iron phosphate and a second doping element; the second material layer is arranged on the side, away from the central axis, of the current collector layer, the second material layer comprises a third active substance, the third active substance comprises lithium iron phosphate and a third doping element, and the mass content of the first doping element is smaller than that of the second doping element and that of the third doping element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrode assembly, a battery and an electrical device. Background Art

[0002] With the continuous development of lithium-ion batteries, lithium iron phosphate is widely used as the positive electrode active material. Its crystal structure belongs to olivine structure, which is safe and stable. At present, lithium-ion batteries are increasingly pursuing high capacity indicators, but this will lead to some problems such as material processing and deterioration of electrical performance, causing lithium precipitation on the surface of the negative electrode, thus affecting the service life of the battery. Summary of the invention

[0003] In view of this, the present application provides an electrode assembly, a battery and an electrical device, wherein the electrode assembly can slow down the occurrence of lithium plating to extend the service life of the battery.

[0004] The present application provides an electrode assembly, the electrode assembly is in a winding structure, the winding structure has a central axis, the electrode assembly includes the positive electrode sheet, the separator and the negative electrode sheet, the separator is located between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet includes: a current collector layer, a first material layer and a second material layer, the first material layer is arranged on the side of the current collector layer facing the central axis, the first material layer includes a first sublayer and a second sublayer, the first sublayer is closer to the central axis than the second sublayer, the first sublayer includes a first active substance, the first active substance is a core-shell structure, the first active substance includes a core and a protective layer, the protective The layer is coated on the periphery of the inner core, the inner core includes lithium iron phosphate and a first doping element, the second sublayer includes a second active material, the second active material includes lithium iron phosphate and a second doping element, and the mass content of the first doping element in the first active material is less than the mass content of the second doping element in the second active material; the second material layer is arranged on the side of the current collector layer away from the central axis, the second material layer includes the third active material, the third active material includes lithium iron phosphate and a third doping element, and the mass content of the first doping element in the first active material is less than the mass content of the third doping element in the third active material.

[0005] Furthermore, the chemical formula of the core of the first active material is LiFe (1-x) M1 x PO4 / C, the chemical formula of the second active material is LiFe (1-y) M2 y PO4 / C, the chemical formula of the third active material is LiFe (1-z) M3 zPO4 / C, wherein M1 is a first doping element, the first doping element is selected from at least one of titanium, vanadium, magnesium or niobium, M2 is a second doping element, the second doping element is selected from at least one of titanium, vanadium, magnesium or niobium, M3 is a third doping element, the third doping element is selected from at least one of titanium, vanadium, magnesium or niobium, and satisfies the relationship: x<y, x<z.

[0006] Furthermore, in the first active material, the range of x is: 0.01≤x≤0.03; and in the second active material, the range of y is: 0.04≤y≤0.06.

[0007] Furthermore, in the third active material, the range of z is: 0.04≤z≤0.06.

[0008] Furthermore, the thickness of the first sub-layer is d1, and the thickness of the second sub-layer is d2, and the relationship is satisfied: 0.1≤d1 / d2≤0.5.

[0009] Furthermore, when the thickness of the second material layer is d3, the relationship is satisfied: 0.85≤(d1+d2) / d3≤1.

[0010] Furthermore, the median particle size D1 of the first active material is in the range of 1.1 μm ≤ D1 ≤ 1.3 μm, the median particle size D2 of the second active material is in the range of 0.8 μm ≤ D2 ≤ 1.0 μm, and the median particle size D3 of the third active material is in the range of 0.8 μm ≤ D3 ≤ 1.0 μm.

[0011] Furthermore, the first active material is a core-shell structure, the first active material includes a core and a protective layer, the protective layer is coated on the periphery of the core, and the chemical formula of the core is LiFe (1-x) M1 x PO4 / C, where x is in the range of 0.02≤x≤0.03.

[0012] Furthermore, the protective layer is an inorganic metal oxide layer, and the protective layer is selected from at least one of an aluminum oxide layer, a calcium oxide layer, and a titanium oxide layer.

[0013] The present application also provides a battery, which includes: an electrode assembly provided in the present application and an electrolyte, wherein the electrolyte is used to wet at least a portion of the electrode assembly.

[0014] The present application also provides an electrical device, which includes: a device body and a battery provided in the present application, and the battery supplies power to the device body.

[0015] In the present application, the first sublayer, the second sublayer, the current collector layer and the second material layer are arranged in sequence, and when the positive electrode sheet, the separator and the negative electrode sheet are wound to form the winding structure, at the bend of the same circle of the winding structure, in the direction from the central axis to the outside, the first sublayer, the second sublayer, the current collector layer and the second material layer are arranged in sequence, then at the corresponding position, that is, at the bend and on any straight line from the central axis to the outside, the curvature of the first sublayer, the curvature of the second sublayer, the curvature of the current collector layer and the curvature of the second material layer gradually decrease. The first active material, the second active material and the third active material are all active materials, and the first doping element, the second doping element and the third doping element are all doping elements. When the doping element is added to the active material, and the mass content of the doping element is large, the bond energy of the Li-O bond in the active material can be weakened, so that the diffusion resistance of lithium ions in the active material is reduced, so that the rate of lithium ion extraction and insertion of the active material is faster, and then the active material can play a higher gram capacity. Therefore, the gram capacity of the active material can be adjusted by adjusting the mass content of the doping element. Specifically, in the present application, if the mass content of the first doping element in the first active substance is less than the mass content of the second doping element in the second active substance, the bond energy of the Li-O bond in the first active substance is stronger, the diffusion resistance of lithium ions in the first active substance is greater, the rate at which the first active substance deintercalates lithium ions is slower, and the gram capacity of the first active substance is lower. On the contrary, if the bond energy of the Li-O bond in the second active substance is weaker, the diffusion resistance of lithium ions in the second active substance is smaller, and the rate at which the second active substance deintercalates lithium ions is faster, then the gram capacity of the second active substance is greater than the gram capacity of the first active substance. When the positive electrode sheet is applied When the electrode assembly is in a winding structure, the first sublayer is closer to the central axis than the second sublayer in the same circle of the winding structure, the curvature of the first sublayer is greater than the curvature of the second sublayer, the area of ​​the first sublayer at the corresponding position of the first sublayer and the second sublayer is smaller, and the gram capacity of the first active substance is less than the gram capacity of the second active substance, which can balance the gram capacity per unit area at the corresponding position of the first sublayer and the second sublayer, that is, the gram capacity per unit area at the corresponding position of the first sublayer and the second sublayer is close to or equal, so as to avoid the first sublayer from extracting too many lithium ions and precipitating them on the surface of the adjacent negative electrode sheet, thereby slowing down the phenomenon of lithium deposition on the surface of the negative electrode sheet. In addition, the second sublayer still has a higher gram capacity, so that the first material layer still has a higher capacity. The first sublayer and the second sublayer cooperate with each other, which not only makes the first material layer have a higher capacity, but also slows down the phenomenon of lithium deposition on the surface of the negative electrode sheet.Similarly, if the mass content of the first doping element in the first active material is less than the mass content of the third doping element in the third active material, the gram capacity of the third active material is greater than the gram capacity of the first active material. In the same circle of the winding structure, the first sublayer is closer to the central axis than the second material layer, the curvature of the first sublayer is greater than the curvature of the second material layer, and the gram capacity of the first active material is less than the gram capacity of the third active material, which can balance the gram capacity per unit area at the corresponding positions of the first material layer and the second material layer to avoid the first sublayer from extracting too many lithium ions and precipitating them on the surface of the adjacent negative electrode sheet, thereby slowing down the phenomenon of lithium precipitation on the surface of the negative electrode sheet. In addition, the second material layer still has a relatively high gram capacity, so that the positive electrode sheet still has a relatively high capacity, and then the positive electrode sheet provided in the present application can not only make the battery have a higher energy density, but also slow down the phenomenon of lithium precipitation on the negative electrode sheet, which is beneficial to prolonging the service life of the battery. Further, in the present embodiment, the protective layer is coated on the periphery of the core, and the protective layer increases the impedance of lithium ions entering and exiting the core, thereby increasing the difficulty of the first active material to deintercalate lithium ions, reducing the performance of the first active material to deintercalate lithium ions, thereby further reducing the gram capacity of the first active material. In the same circle of the winding structure, the gram capacity per unit area of ​​the first sublayer can be reduced to balance the gram capacity per unit area at the corresponding position of the first sublayer and the second sublayer and / or the second material layer, thereby avoiding the first sublayer from deintercalating too many lithium ions, so as to slow down the phenomenon of lithium precipitation on the surface of the negative electrode plate, and extend the service life of the battery. By setting the protective layer and setting the mass content of the first doping element to be low, the two play a synergistic role, so that there is a difference in the lithium ion diffusion capacity of the positive electrode plate close to the central axis and the side away from the central axis, that is, the lithium ion diffusion capacity of the positive electrode plate close to the central axis is worse than the lithium ion diffusion capacity of the positive electrode plate away from the central axis, so as to better slow down the occurrence of lithium precipitation. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 A schematic diagram of a top view of a battery according to an embodiment of the present application;

[0018] Figure 2 A schematic cross-sectional structure diagram of a positive electrode sheet according to an embodiment of the present application;

[0019] Figure 3 This is a schematic structural diagram of a first active material according to an embodiment of the present application;

[0020] Figure 4 A partial cross-sectional structural schematic diagram of a battery according to an embodiment of the present application;

[0021] Figure 5 An electron scanning microscope of the first active material according to an embodiment of the present application;

[0022] Figure 6 An electron scanning microscope of the second active material of one embodiment of the present application;

[0023] Figure 7 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application;

[0024] Figure 8 This is a circuit block diagram of an electrical device according to an embodiment of the present application.

[0025] Description of reference numerals:

[0026] 100-electrode assembly, 101-central axis, 110-positive electrode plate, 111-current collector layer, 112-first material layer, 1121-first sublayer, 1122-second sublayer, 113-second material layer, 120-diaphragm, 130-negative electrode plate, 140-first active material, 141-core, 142-protective layer, 200-battery, 210-electrolyte, 220-shell, 221-accommodating chamber, 300-electrical equipment, 310-equipment body. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0029] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0030] With the continuous development of lithium-ion batteries, lithium iron phosphate is widely used in positive electrode active materials. Its crystal structure belongs to olivine structure, which is safe and stable. At present, lithium-ion batteries are increasingly pursuing high capacity indicators, but this will lead to some problems such as material processing and deterioration of electrical performance. In addition, the positive electrode sheet, diaphragm and negative electrode sheet form a winding structure. The curvature of the inner side of the winding structure is large, which leads to different contents of active lithium ions inside and outside the winding structure. The positive electrode sheet near the inner side of the winding structure precipitates more lithium ions per unit area, while the graphite used in the negative electrode sheet expands greatly, resulting in a smaller distance between the negative electrode sheet and the positive electrode sheet, which causes lithium precipitation on the surface of the negative electrode sheet and ultimately affects the service life of the battery.

[0031] See also Figures 1 to 3The present application provides an electrode assembly 100, the electrode assembly 100 is in a winding structure, the winding structure has a central axis 101, the electrode assembly 100 includes the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130, the separator 120 is located between the positive electrode sheet 110 and the negative electrode sheet 130, the positive electrode sheet 110 includes: a current collector layer 111, a first material layer 112 and a second material layer 113, the first material layer 112 is arranged on the side of the current collector layer 111 facing the central axis 101, the first material layer 112 includes a first sublayer 1121 and a second sublayer 1122, the first sublayer 1121 is closer to the central axis 101 than the second sublayer 1122, the first sublayer 1121 includes a first active material 140, and the first active material 140 is a core-shell structure The first active material 140 includes a core 141 and a protective layer 142, the protective layer 142 is coated on the periphery of the core 141, the first active material 140 includes lithium iron phosphate and a first doping element, the second sublayer 1122 includes a second active material, the second active material includes lithium iron phosphate and a second doping element, and the mass content of the first doping element in the first active material 140 is less than the mass content of the second doping element in the second active material; the second material layer 113 is arranged on the side of the current collector layer 111 away from the central axis 101, the second material layer 113 includes the third active material, the third active material includes lithium iron phosphate and a third doping element, and the mass content of the first doping element in the first active material 140 is less than the mass content of the third doping element in the third active material.

[0032] It can be understood that the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are stacked and then wound to form the winding structure. Specifically, in the same circle of the winding structure, in the direction from the central axis 101 to the outside, the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are arranged in sequence.

[0033] It can be understood that the first material layer 112 , the current collector layer 111 and the second material layer 113 are stacked in sequence and then wound, and the first material layer 112 is closer to the central axis 101 of the winding structure than the second material layer 113 .

[0034] It can be understood that the first sublayer 1121 , the second sublayer 1122 , the current collector layer 111 and the second material layer 113 are stacked in sequence, and the first sublayer 1121 is closer to the central axis 101 of the winding structure than the second sublayer 1122 .

[0035] Optionally, the first active material 140 includes lithium iron phosphate and a first doping element, and the first doping element is used to dope the lithium iron phosphate; the second active material includes lithium iron phosphate and a second doping element, and the second doping element is used to dope the lithium iron phosphate; the third active material includes lithium iron phosphate and a third doping element, and the third doping element is used to dope the lithium iron phosphate. In other words, the raw materials of the first active material 140, the second active material, and the third active material all include lithium iron phosphate.

[0036] In this embodiment, the first sublayer 1121, the second sublayer 1122, the current collector layer 111 and the second material layer 113 are arranged in sequence, and when the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are wound to form the wound structure, at the bending point of the same turn of the wound structure, in the direction pointing outward from the central axis 101, the first sublayer 1121, the second sublayer 1122, the current collector layer 111 and the second material layer 113 are arranged in sequence, then at the corresponding position, that is, at the bending point and on any straight line pointing outward from the central axis 101, the curvature of the first sublayer 1121, the curvature of the second sublayer 1122, the curvature of the current collector layer 111 and the curvature of the second material layer 113 gradually decrease. The first active material 140, the second active material and the third active material are all active materials, and the first doping element, the second doping element and the third doping element are all doping elements. When the doping element is added to the active material, and the mass content of the doping element is large, the bond energy of the Li-O bond in the active material can be weakened, so that the diffusion resistance of lithium ions in the active material is reduced, so that the rate of lithium ion extraction of the active material is faster, and then the active material can exert a higher gram capacity. Therefore, the gram capacity of the active material can be adjusted by adjusting the mass content of the doping element.Specifically, in the embodiment of the present application, the mass content of the first doping element in the first active material 140 is less than the mass content of the second doping element in the second active material, then the bond energy of the Li-O bond in the first active material 140 is stronger, the diffusion resistance of lithium ions in the first active material 140 is greater, the rate at which the first active material 140 deintercalates lithium ions is slower, and the gram capacity of the first active material 140 is lower. On the contrary, the bond energy of the Li-O bond in the second active material is weaker, the diffusion resistance of lithium ions in the second active material is smaller, and the rate at which the second active material deintercalates lithium ions is faster, so that the gram capacity of the second active material is greater than the gram capacity of the first active material 140. When the positive electrode sheet 110 is applied to the electrode assembly 100 and the electrode assembly 100 is rolled When the structure is wound, in the same circle of the winding structure, the first sublayer 1121 is closer to the central axis 101 than the second sublayer 1122, the curvature of the first sublayer 1121 is greater than the curvature of the second sublayer 1122, the area of ​​the first sublayer 1121 at the corresponding position of the first sublayer 1121 and the second sublayer 1122 is smaller, and the gram capacity of the first active material 140 is less than the gram capacity of the second active material, which can balance the gram capacity per unit area at the corresponding position of the first sublayer 1121 and the second sublayer 1122, that is, the gram capacity per unit area at the corresponding position of the first sublayer 1121 and the second sublayer 1122 is close to or equal, so as to avoid the first sublayer 1121 from extracting too many lithium ions and precipitating them on the surface of the adjacent negative electrode sheet 130, thereby slowing down the phenomenon of lithium precipitation on the surface of the negative electrode sheet 130. In addition, the second sublayer 1122 still has a relatively high gram capacity, so that the first material layer 112 still has a relatively high capacity. The first sublayer 1121 and the second sublayer 1122 cooperate with each other, so that the first material layer 112 has a higher capacity and can slow down the lithium deposition on the surface of the negative electrode sheet 130. Similarly, if the mass content of the first doping element in the first active material 140 is less than the mass content of the third doping element in the third active material, the gram capacity of the third active material is greater than the gram capacity of the first active material 140. In the same circle of the winding structure, the first sublayer 1121 is closer to the central axis 101 than the second material layer 113, the curvature of the first sublayer 1121 is greater than the curvature of the second material layer 113, and the gram capacity of the first active material 140 is less than the gram capacity of the third active material. The gram capacity per unit area at the corresponding positions of the first material layer 112 and the second material layer 113 can be balanced to avoid the first sublayer 1121 from extracting too many lithium ions and precipitating them on the surface of the adjacent negative electrode sheet 130, thereby slowing down the lithium deposition on the surface of the negative electrode sheet 130.In addition, the second material layer 113 still has a relatively high gram capacity, so that the positive electrode plate 110 still has a relatively high capacity, and then the positive electrode plate 110 provided in this embodiment can not only make the battery 200 have a relatively high energy density, but also slow down the lithium precipitation phenomenon of the negative electrode plate 130, which is beneficial to prolong the service life of the battery 200. Further, in this embodiment, the protective layer 142 is coated on the periphery of the core 141, and the protective layer 142 increases the impedance of lithium ions entering and exiting the core 141, thereby increasing the difficulty of the first active material 140 to deintercalate lithium ions, reducing the performance of the first active material 140 to deintercalate lithium ions, thereby further reducing the gram capacity of the first active material 140. In the same circle of the winding structure, the gram capacity per unit area of ​​the first sublayer 1121 can be reduced to balance the gram capacity per unit area at the corresponding positions of the first sublayer 1121 and the second sublayer 1122 and / or the second material layer 113, so as to avoid the first sublayer 1121 from extracting too many lithium ions, so as to slow down the lithium precipitation on the surface of the negative electrode plate 130, and extend the service life of the battery 200. By setting the protective layer 142 and setting the mass content of the first doping element to be relatively low, the two play a synergistic role, so that there is a difference in the lithium ion diffusion capacity of the positive electrode plate 110 on the side close to the central axis 101 and the side away from the central axis 101, that is, the lithium ion diffusion capacity of the positive electrode plate 110 on the side close to the central axis 101 is worse than the lithium ion diffusion capacity of the positive electrode plate 110 on the side away from the central axis 101, so as to better slow down the occurrence of lithium precipitation.

[0037] It can be understood that in the terminology of the present application, when the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are stacked and wound around the central axis 101 for multiple turns, when the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are wound around the central axis 101 for the same number of turns, it means "in the same turn of the winding structure".

[0038] It can be understood that in the terminology of this application, the "gram capacity" of an active material refers to the ratio of the capacitance that the active material can release to the mass of the active material. The higher the gram capacity of the active material, the better the rate and performance of the active material in deintercalating and extracting lithium ions.

[0039] It can be understood that the winding structure is wound around the central axis 101, with the innermost circle closest to the central axis 101 and the outermost circle farthest from the central axis 101, and the number of winding turns gradually increases in the direction from the innermost circle to the outermost circle; assuming that in the nth circle of the winding structure, the first sublayer 1121 releases too many lithium ions, and during the charging and discharging process of the battery 200, the volume of the negative electrode sheet 130 expands, so that the distance between the first sublayer 1121 of the nth circle and the negative electrode sheet 130 of the n-1th circle becomes smaller, so that the excessive lithium ions precipitated from the first sublayer 1121 of the nth circle will be precipitated on the surface of the negative electrode sheet 130 of the n-1th circle of the winding structure.

[0040] Optionally, the first doping element is selected from metal elements. The second doping element is selected from metal elements. The third doping element is selected from metal elements. It can be understood that the first doping element is doped into at least one of the lithium site and the iron site in the first active material 140; the second doping element is doped into at least one of the lithium site and the iron site in the second active material; and the third doping element is doped into at least one of the lithium site and the iron site in the third active material.

[0041] Optionally, the ionic resistivity of the first sublayer 1121 is greater than the ionic resistivity of the second sublayer 1122, and the ionic resistivity of the first sublayer 1121 is greater than the ionic resistivity of the second material layer 113. In this embodiment, the rate at which the first active material 140 of the first sublayer 1121 deintercalates lithium ions is less than the rate at which the second active material of the second sublayer 1122 deintercalates lithium ions, and the rate at which the first active material 140 of the first sublayer 1121 deintercalates lithium ions is less than the rate at which the third active material in the second material layer 113 deintercalates lithium ions, which can effectively slow down the lithium precipitation phenomenon of the negative electrode sheet 130 and improve the cycle performance of the battery 200.

[0042] In some embodiments, the chemical formula of the core 141 of the first active material 140 is LiFe (1-x) M1 x PO4 / C, the chemical formula of the second active material is LiFe (1-y) M2 y PO4 / C, the chemical formula of the third active material is LiFe (1-z) M3 z PO4 / C, wherein M1 is a first doping element, the first doping element is selected from at least one of titanium (Ti), vanadium (V), magnesium (Mg) or niobium (Nb), M2 is a second doping element, the second doping element is selected from at least one of titanium, vanadium, magnesium or niobium, M3 is a third doping element, the third doping element is selected from at least one of titanium, vanadium, magnesium or niobium, and satisfies the relationship: x<y, x<z.

[0043] It can be understood that x represents the mass content of the first doping element of the core 141 in the first active material 140, y represents the mass content of the second doping element in the second active material, and z represents the mass content of the third doping element in the third active material.

[0044] It can be understood that in some embodiments, the first doping element, the second doping element and the third doping element are selected from the same one of titanium, vanadium, magnesium or niobium. In other embodiments, the first doping element, the second doping element and the third doping element are selected from different ones of titanium, vanadium, magnesium or niobium.

[0045] It can be understood that the chemical formula of the core 141 of the first active material 140 is LiFe (1-x) M1 x PO4 / C, the first active material 140 is a mixture of lithium iron phosphate doped with the first doping element and carbon.

[0046] It can be understood that the chemical formula of the second active material is LiFe (1-y) M2 y PO4 / C, the second active material is a mixture of lithium iron phosphate doped with the second doping element and carbon.

[0047] It can be understood that the chemical formula of the third active material is LiFe (1-z) M3 z PO4 / C, the third active material is a mixture of lithium iron phosphate doped with a third doping element and carbon.

[0048] In this embodiment, the chemical formula of the core 141 of the first active material 140 is LiFe (1-x) M1 x PO4 / C, the chemical formula of the second active material is LiFe (1-y) M2 yPO4 / C, and the relationship x<y is satisfied, then the mass content of the first doping element is less than the mass content of the second doping element, and the resistance of lithium ion diffusion in the first active material 140 is greater than the resistance of diffusion in the second active material, so that the gram capacity of the first active material 140 is less than the gram capacity of the second active material, which can balance the gram capacity per unit area at the corresponding positions of the first sublayer 1121 and the second sublayer 1122, so as to avoid excessive lithium ions being extracted from the first sublayer 1121 and precipitated on the surface of the adjacent negative electrode sheet 130, thereby slowing down the phenomenon of lithium precipitation on the surface of the negative electrode sheet 130. In addition, the second sublayer 1122 still has a relatively high gram capacity, so that the first material layer 112 still has a relatively high capacity. Similarly, the chemical formula of the third active material is LiFe (1-z) M3 z PO4 / C, and satisfies the relationship x<z, then the mass content of the first doping element is less than the mass content of the third doping element, and the resistance of lithium ion diffusion in the first active material 140 is greater than the resistance of diffusion in the third active material, so that the gram capacity of the first active material 140 is less than the gram capacity of the third active material. In the same circle of the winding structure, the first sublayer 1121 is closer to the central axis 101 than the second material layer 113, and the curvature of the first sublayer 1121 is greater than the curvature of the second material layer 113. The gram capacity of the first active material 140 is less than the gram capacity of the third active material, which can balance the gram capacity per unit area at the corresponding positions of the first material layer 112 and the second material layer 113, so as to avoid the first sublayer 1121 from extracting too many lithium ions and precipitating them on the surface of the adjacent negative electrode sheet 130, thereby slowing down the lithium precipitation on the surface of the negative electrode sheet 130. In addition, the second material layer 113 still has a relatively high gram capacity, so that the positive electrode plate 110 still has a relatively high capacity, and then the positive electrode plate 110 provided in this embodiment can not only make the battery 200 have a higher energy density, but also slow down the lithium plating phenomenon of the negative electrode plate 130, which is beneficial to extend the service life of the battery 200.

[0049] Preferably, in some embodiments, the second active material is the same as the third active material, in other words, the second active material and the third active material satisfy the relationship: y=z, and the second doping element M2 and the third doping element M3 are selected from the same element.

[0050] In this embodiment, when the second active substance is the same as the third active substance, the active materials in the second sublayer 1122 and the second material layer 113 are the same, which is beneficial to improving the consistency of the positive electrode sheet 110. On the one hand, it is convenient for processing the positive electrode sheet 110, and on the other hand, it is beneficial to improve the cycle performance of the battery 200.

[0051] In some embodiments, in the first active material 140 , the range of x is: 0.01≤x≤0.03.

[0052] Specifically, the value of x may be, but is not limited to, 0.01, 0.012, 0.014, 0.015, 0.018, 0.02, 0.021, 0.022, 0.023, 0.024, 0.025, 0.026, 0.027, 0.028, 0.029, and 0.03.

[0053] In the first active material 140 provided in this embodiment, when x satisfies the range of 0.01≤x≤0.03, the mass content of the first doping element is within a reasonable range. On the one hand, in the first active material 140, the bond energy of the Li-O bond is within a reasonable range, the diffusion resistance of lithium ions in the first active material 140 is small, the rate of deintercalation of lithium ions by the first active material 140 is slow, and the gram capacity of the first active material 140 is low. In the same turn of the winding structure, the gram capacity per unit area of ​​the first sublayer 1121 can be reduced to balance the gram capacity per unit area at the corresponding positions of the first sublayer 1121 and the second sublayer 1122 and / or the second material layer 113, thereby avoiding excessive deintercalation of lithium ions from the first sublayer 1121, slowing down the phenomenon of lithium deposition on the surface of the negative electrode plate 130, and extending the service life of the battery 200. On the other hand, the gram capacity of the first active material 140 is not too low to make the capacity of the positive electrode plate 110 too low, so that the battery 200 has both high capacity, energy density and good safety performance. When the value of x is too large, the mass content of the first doping element is too large, then in the first active material 140, the bond energy of the Li-O bond is still weak, the diffusion resistance of lithium ions in the first active material 140 is too small, the rate of lithium ion extraction and insertion of the first active material 140 is too fast, and the gram capacity of the first active material 140 is too high. In the winding structure, the first active material 140 of the first sublayer 1121 releases too much lithium ions to form lithium precipitation on the surface of the adjacent negative electrode plate 130, thereby making the cycle performance of the battery 200 too poor. When the value of x is too small, the mass content of the first doping element is too small, and accordingly, the gram capacity of the first active material 140 is too low. Although it can slow down the lithium deposition phenomenon of the negative electrode plate 130 to a certain extent, it also makes the capacity of the positive electrode plate 110 too low, thereby making the capacity and energy density of the battery 200 lower.

[0054] Preferably, in the first active material 140 , the range of x is: 0.02≤x≤0.03.

[0055] In some embodiments, in the second active material, the range of y is: 0.04≤y≤0.06.

[0056] Specifically, the value of y may be, but is not limited to, 0.04, 0.041, 0.042, 0.043, 0.044, 0.045, 0.046, 0.047, 0.048, 0.049, 0.05, 0.052, 0.054, 0.056, 0.058, and 0.06, etc.

[0057] In the second active material provided in this embodiment, when y satisfies the range of 0.04≤y≤0.06, the mass content of the second doping element is within a reasonable range. In the second active material, the second doping element causes lattice distortion of lithium iron phosphate, and the degree of lattice distortion is within a reasonable range. The bond energy of the Li-O bond in the second active material doped with the second doping element is weak, the diffusion resistance of lithium ions in the second active material is small, and the second active material deintercalates lithium ions at a faster rate, so that the second active material has a larger gram capacity, so that the first material layer 112 has a larger gram capacity, and the positive electrode plate 110 has a larger capacity. When the electrode assembly 100 is applied to the battery 200, the battery 200 has a higher capacity and energy density. When the value of y is too large, the mass content of the second doping element is too large. As is known, the amount of distortion of the crystal structure is limited. In the second active material, excessive second doping elements may cause the second active material to produce heterophase compounds, thereby reducing the performance of the second active material in extracting and inserting lithium ions, and then reducing the capacity performance of the positive electrode plate 110 and the electrode assembly 100, so that the capacity and energy density of the battery 200 are low. When the value of y is too small, the mass content of the second doping element is too small, and the gram capacity of the second active material of the second sublayer 1122 is too low. In the case where the gram capacity of the first active material 140 is low, the gram capacity of the first material layer 112 is too low, thereby reducing the capacity of the positive electrode plate 110, and then the capacity and energy density of the battery 200 are too low, reducing the performance of the battery 200.

[0058] Preferably, in the second active material, the range of y is: 0.04≤y≤0.05.

[0059] In some embodiments, in the third active material, the range of z is: 0.04≤z≤0.06.

[0060] Specifically, the value of z may be, but is not limited to, 0.04, 0.041, 0.042, 0.043, 0.044, 0.045, 0.046, 0.047, 0.048, 0.049, 0.05, 0.052, 0.054, 0.056, 0.058, and 0.06, etc.

[0061] In the third active material provided in this embodiment, when z satisfies the range of 0.04≤z≤0.06, the mass content of the third doping element is within a reasonable range, in the third active material, the third doping element causes lattice distortion of lithium iron phosphate, and the degree of lattice distortion is within a reasonable range, the bond energy of Li-O bond in the third active material doped with the third doping element is weak, the diffusion resistance of lithium ions in the third active material is small, and the rate of lithium ion deintercalation of the third active material is fast, so that the third active material has a larger gram capacity, so that the second material layer 113 has a larger gram capacity, and the positive electrode plate 110 has a larger capacity. When the electrode assembly 100 is applied to the battery 200, the battery 200 has a higher capacity and energy density. When the value of z is too large, the mass content of the third doping element is too large. In the third active material, excessive third doping elements may cause the third active material to produce heterophase compounds, thereby reducing the performance of the third active material in extracting and inserting lithium ions, and then reducing the capacity performance of the positive electrode plate 110 and the electrode assembly 100, so that the capacity and energy density of the battery 200 are low. When the value of z is too small, the mass content of the third doping element is too small, and the gram capacity of the third active material of the second material layer 113 is too low. In the case where the capacity of the first material layer 112 is relatively low, if the gram capacity of the second material layer 113 is too low, the capacity of the positive electrode plate 110 is too low, and then the capacity and energy density of the battery 200 are too low, which reduces the performance of the battery 200.

[0062] Preferably, in the third active material, the range of z is: 0.04≤z≤0.05.

[0063] In some embodiments, the protective layer 142 is an inorganic metal oxide layer, and the protective layer 142 is selected from at least one of an aluminum oxide layer, a calcium oxide layer, and a titanium oxide layer.

[0064] In this embodiment, the protective layer 142 is an inorganic metal oxide layer, and the protective layer 142 is selected from at least one of an aluminum oxide layer, a calcium oxide layer, and a titanium oxide layer. The protective layer 142 has a relatively low ionic conductivity to further reduce the rate at which lithium ions are embedded in or extracted from the core 141, thereby reducing the gram capacity of the first active material 140. In the same circle of the winding structure, the gram capacity per unit area of ​​the first sublayer 1121 can be reduced to balance the gram capacity per unit area at the corresponding positions of the first sublayer 1121 and the second sublayer 1122 and / or the second material layer 113, thereby avoiding the first sublayer 1121 from extracting too many lithium ions, slowing down the phenomenon of lithium deposition on the surface of the negative electrode plate 130, and extending the service life of the battery 200.

[0065] See also Figure 2 In some embodiments, the thickness of the first sub-layer 1121 is d1, and the thickness of the second sub-layer 1122 is d2, then the relationship is satisfied: 0.1≤d1 / d2≤0.5.

[0066] Specifically, the value of d1 / d2 can be, but is not limited to, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, 0.42, 0.45, 0.48, 0.49 and 0.5, etc.

[0067] In this embodiment, when the thickness d1 of the first sublayer 1121 and the thickness d2 of the second sublayer 1122 satisfy the relationship 0.1≤d1 / d2≤0.5, the thickness of the first sublayer 1121 and the thickness of the second sublayer 1122 are within a reasonable range, the first sublayer 1121 includes the first active material 140, and the mass content of the first doping element of the first active material 140 is low, so that the gram capacity of the first active material 140 is low, and the capacity of the first sublayer 1121 is low. The second sublayer 1122 includes the second active material, and the mass content of the second doping element of the second active material is high, so that the gram capacity of the second active material is high, and the capacity of the second sublayer 1122 is high. On the one hand, in the winding structure, the speed of the first sublayer 1121 to deintercalate lithium ions can be slowed down, and the first sublayer 1121 is prevented from deintercalating too many lithium ions and precipitating on the surface of the negative electrode sheet 130, thereby slowing down the lithium precipitation phenomenon on the surface of the negative electrode sheet 130, and improving the safety performance of the battery 200. On the other hand, it can avoid that the first sublayer 1121 is too thick and the capacity of the first material layer 112 is too low, so that the positive electrode plate 110 still has a relatively high capacity, so that the electrode assembly 100 has both high capacity and high safety performance. When the value of d1 / d2 is too large, the thickness of the first sublayer 1121 is too large or the thickness of the second sublayer 1122 is too small, the capacity of the first sublayer 1121 is low and the first sublayer 1121 occupies too much space in the first material layer 112, and the capacity of the second sublayer 1122 is high but the space occupied by the second sublayer 1122 in the first material layer 112 is too small, thereby reducing the capacity of the positive electrode plate 110. Although it can better slow down the lithium deposition phenomenon on the surface of the negative electrode plate 130, when the electrode assembly 100 is applied to the battery 200, the capacity and energy density of the battery 200 are too low. When the value of d1 / d2 is too small, the thickness of the first sublayer 1121 is too small or the thickness of the second sublayer 1122 is too large. Accordingly, in the positive electrode sheet 110, the first active substance 140 is less, and the first sublayer 1121 can hardly play the role of slowing down the occurrence of lithium precipitation. In the same circle of the winding structure, the first material layer 112 and the second material layer 113 both precipitate more lithium ions, which makes the gram capacity per unit area of ​​the first material layer 112 too much. The excessive lithium ions precipitated from the first material layer 112 are easily precipitated on the surface of the negative electrode sheet 130, thereby affecting the cycle performance of the battery 200.

[0068] Optionally, the thickness d1 of the first sublayer 1121 is in the range of 3 μm≤d1≤25 μm.

[0069] Specifically, the thickness d1 of the first sublayer 1121 may be, but is not limited to, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 17 μm, 18 μm, 20 μm, 21 μm, 23 μm, 25 μm, etc.

[0070] In this embodiment, when the thickness d1 of the first sublayer 1121 satisfies the range of 3μm≤d1≤25μm, the thickness of the first sublayer 1121 is within a reasonable range, the first sublayer 1121 includes the first active material 140, and the mass content of the first doping element of the first active material 140 is relatively low, so that the gram capacity of the first active material 140 is relatively low. On the one hand, the gram capacity of the first active material 140 of the first sublayer 1121 is relatively low, so that in the winding structure, the speed of the first sublayer 1121 to deintercalate lithium ions can be slowed down, and the first sublayer 1121 is prevented from deintercalating too many lithium ions and precipitating on the surface of the negative electrode sheet 130, thereby slowing down the lithium precipitation phenomenon on the surface of the negative electrode sheet 130 and improving the safety performance of the battery 200. On the other hand, it can be avoided that the first sublayer 1121 is too thick, which makes the capacity of the first material layer 112 too low, and then the positive electrode sheet 110 still has a relatively high capacity, so that the electrode assembly 100 has both high capacity and high safety performance. When the thickness of the first sublayer 1121 is too large, the first sublayer 1121 occupies too much space of the first material layer 112, so that the capacity of the first material layer 112 is low, thereby reducing the capacity of the positive electrode sheet 110. Although it can better slow down the lithium precipitation phenomenon on the surface of the negative electrode sheet 130, when the electrode assembly 100 is applied to the battery 200, the capacity and energy density of the battery 200 are too low. When the thickness of the first sublayer 1121 is too small, then correspondingly, in the positive electrode sheet 110, the first active material 140 is less, and the first sublayer 1121 is difficult to play a role in slowing down the occurrence of lithium precipitation. In the same circle of the winding structure, the first material layer 112 and the second material layer 113 both precipitate more lithium ions, which makes the gram capacity per unit area of ​​the first material layer 112 too much, and the excessive lithium ions precipitated by the first material layer 112 are easily precipitated on the surface of the negative electrode sheet 130, thereby affecting the cycle performance of the battery 200.

[0071] Optionally, the thickness d2 of the second sub-layer 1122 is in the range of 35 μm≤d2≤55 μm.

[0072] Specifically, the thickness d2 of the second sublayer 1122 can be, but is not limited to, 35 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm, 45 μm, 47 μm, 48 μm, 50 μm, 52 μm, 53 μm, 54 μm, 55 μm, etc.

[0073] In this embodiment, when the thickness d2 of the second sublayer 1122 satisfies the range of 35μm≤d2≤55μm, the thickness of the second sublayer 1122 is within a reasonable range. On the one hand, when the capacity of the first sublayer 1121 is low, the mass content of the second doping element of the second active material of the second sublayer 1122 is high, so that the second active material has a higher gram capacity, so that the second sublayer 1122 has a higher capacity, so that the first material layer 112 can have both a higher capacity and can slow down the occurrence of lithium precipitation. On the other hand, it can avoid that the second sublayer 1122 is too thick, which leads to an excessive thickness of the positive electrode sheet 110, so that the electrode assembly 100 has better performance. When the thickness of the second sublayer 1122 is too large, the thickness of the positive electrode sheet 110 will be too large, which reduces the performance of the electrode assembly 100. When the thickness of the second sublayer 1122 is too small, then when the capacity of the first sublayer 1121 is low, the capacity of the second sublayer 1122 is also low, so that the capacity of the first material layer 112 is too low, which is not conducive to the improvement of the capacity of the positive electrode plate 110, and ultimately reduces the capacity performance and energy density of the battery 200.

[0074] In some embodiments, the thickness of the second material layer 113 is d3, which satisfies the relationship: 0.85≤(d1+d2) / d3≤1.

[0075] It can be understood that d1+d2 represents the thickness of the first material layer 112 .

[0076] It can be understood that the thickness of the first material layer 112 is less than or equal to the thickness of the second material layer 113 .

[0077] Specifically, the value of (d1+d2) / d3 can be, but is not limited to, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99 and 1, etc.

[0078] In this embodiment, when the electrode assembly 100 satisfies the relationship 0.85≤(d1+d2) / d3≤1, the thickness of the second material layer 113 and the thickness of the first material layer 112 are both within a reasonable range. On the one hand, the capacity utilization of the first material layer 112 and the capacity utilization of the second material layer 113 can be different, that is, in the same circle of the winding structure, the rate of lithium ion deintercalation of the first material layer 112 is lower than the rate of lithium ion deintercalation of the second material layer 113, so as to avoid the first sublayer 1121 of the first material layer 112 from precipitating too much lithium ions and precipitating on the surface of the negative electrode sheet 130, so that the positive electrode sheet 110 has better safety performance. On the other hand, the first material layer 112 and the second material layer 113 still maintain a relatively high capacity, so that the positive electrode sheet 110 has a relatively high capacity, so that when the electrode assembly 100 is applied to the battery 200, the battery 200 has a relatively high capacity and energy density. When (d1+d2) / d3 is too large, the thickness of the first material layer 112 is too large, and the thickness of the second material layer 113 is too small. The first material layer 112 includes a first sublayer 1121 and a second sublayer 1122. If the first sublayer 1121 is too large, it may cause the capacity of the first material layer 112 to be too low, and the thickness of the second material layer 113 is too small. Correspondingly, the capacity of the positive electrode sheet 110 is low, which reduces the capacity and energy density of the battery 200 when the electrode assembly 100 is applied to the battery 200. When (d1+d2) / d3 is too small, the thickness of the first material layer 112 is too small, and the thickness of the second material layer 113 is too large. If the thickness of the first sublayer 1121 in the first material layer 112 is too small, the first sublayer 1121 will hardly play the role of slowing down the occurrence of lithium precipitation. In the same circle of the winding structure, the first material layer 112 and the second material layer 113 will both precipitate more lithium ions, which makes the gram capacity per unit area of ​​the first material layer 112 too much. The excessive lithium ions precipitated from the first material layer 112 are easily precipitated on the surface of the negative electrode 130, thereby affecting the cycle performance of the battery 200.

[0079] Optionally, a thickness d3 of the second material layer 113 is in the range of 30 μm≤d3≤60 μm.

[0080] Specifically, the thickness d3 of the second material layer 113 may be, but is not limited to, 30 μm, 32 μm, 35 μm, 38 μm, 40 μm, 42 μm, 45 μm, 50 μm, 52 μm, 53 μm, 56 μm, 60 μm, etc.

[0081] In this embodiment, when the thickness d3 of the second material layer 113 satisfies the range of 30 μm ≤ d3 ≤ 60 μm, the thickness of the second material layer 113 is within a reasonable range, and the second material layer 113 has a suitable capacity, so that when the electrode assembly 100 is applied to the battery 200, the battery 200 has a higher capacity and energy density. When the thickness of the second material layer 113 is too large, the thickness of the positive electrode sheet 110 will be too large, reducing the performance of the electrode assembly 100. When the thickness of the second material layer 113 is too small, the capacity of the second material layer 113 is too low, which is not conducive to the improvement of the capacity of the positive electrode sheet 110, and ultimately reduces the capacity performance and energy density of the battery 200.

[0082] In some embodiments, the median particle size D1 of the first active material 140 is in the range of 1.1 μm≤D1≤1.3 μm.

[0083] Specifically, the median particle size D1 of the first active material 140 may be, but is not limited to, 1.1 μm, 1.11 μm, 1.13 μm, 1.15 μm, 1.18 μm, 1.2 μm, 1.21 μm, 1.23 μm, 1.24 μm, 1.26 μm, 1.28 μm, 1.3 μm, etc.

[0084] It can be understood that, in some embodiments, when the mass content of the first doping element in the first active material 140 is low, the median particle size of the first active material 140 is large.

[0085] In this embodiment, when the median particle size D1 of the first active material 140 satisfies the range of 1.1μm≤D1≤1.3μm, the median particle size of the first active material 140 is within a reasonable range. On the one hand, it is convenient to set the first active material 140 in the first sub-layer 1121 so that the first sub-layer 1121 can play a role in slowing down the occurrence of lithium plating. On the other hand, the median particle size of the first active material 140 is larger than the median particle size of the second active material and the median particle size of the third active material, and the median particle size of the first active material 140 is negatively correlated with the mass content of the first doping element. In other words, the mass content of the first doping element in the first active material 140 is low and the mass content of the first doping element is also within a reasonable range. In the first active material 140, the bond energy of the Li-O bond is within a reasonable range, the diffusion resistance of lithium ions in the first active material 140 is small, the rate of lithium ion deintercalation of the first active material 140 is slow, and the gram capacity of the first active material 140 is low. In the same circle of the winding structure, the gram capacity per unit area of ​​the first sublayer 1121 can be reduced to balance the gram capacity per unit area at the corresponding positions of the first sublayer 1121 and the second sublayer 1122 and / or the second material layer 113, thereby avoiding excessive lithium ion deintercalation from the first sublayer 1121, slowing down the lithium deposition on the surface of the negative electrode plate 130, and extending the service life of the battery 200. In addition, the gram capacity of the first active material 140 is not too low to make the capacity of the positive electrode plate 110 too low, so that the battery 200 has both high capacity, energy density and good safety performance. When the median particle size of the first active material 140 is too large, on the one hand, it is not conducive to setting the first active material 140 in the first sublayer 1121. On the other hand, if the median particle size of the first active material 140 is too large, then the mass content of the first doping element in the first active material 140 is too low. Although it can slow down the lithium precipitation phenomenon of the negative electrode plate 130 to a certain extent, it also makes the capacity of the positive electrode plate 110 too low, so that the capacity and energy density of the battery 200 are low. When the median particle size of the first active material 140 is too small, the mass content of the first doping element in the first active material 140 is too high, and the gram capacity of the first active material 140 is too high. In the winding structure, excessive lithium ions released from the first active material 140 of the first sublayer 1121 form lithium deposition on the surface of the adjacent negative electrode sheet 130, thereby making the cycle performance of the battery 200 too poor.

[0086] In some embodiments, the median particle size D2 of the second active material is in the range of 0.8 μm≤D2≤1.0 μm.

[0087] Specifically, the median particle size D2 of the second active material may be, but is not limited to, 0.8 μm, 0.82 μm, 0.83 μm, 0.85 μm, 0.88 μm, 0.9 μm, 0.92 μm, 0.93 μm, 0.95 μm, 0.96 μm, 0.97 μm, 0.99 μm, 1.0 μm, etc.

[0088] It can be understood that, in some embodiments, when the mass content of the second doping element in the second active material is higher, the median particle size of the first active material 140 is smaller.

[0089] In this embodiment, when the median particle size D2 of the second active material satisfies the range of 0.8 μm ≤ D2 ≤ 1.0 μm, the median particle size of the second active material is within a reasonable range. On the one hand, it is convenient to set the second active material in the second sublayer 1122, so that the second sublayer 1122 cooperates with the first sublayer 1121, so that the first material layer 112 can not only slow down the lithium precipitation phenomenon on the surface of the negative electrode plate 130, but also has a higher capacity. On the other hand, the median particle size of the second active material is negatively correlated with the mass content of the second doping element. In other words, the mass content of the second doping element in the second active material is high and the mass content of the second doping element is also within a reasonable range. The bond energy of the Li-O bond in the second active material doped with the second doping element is weak, the diffusion resistance of lithium ions in the second active material is small, and the second active material deintercalates lithium ions at a faster rate, so that the second active material has a larger gram capacity, so that the first material layer 112 has a larger gram capacity, and the positive electrode plate 110 has a larger capacity. When the electrode assembly 100 is applied to a battery 200, the battery 200 has a relatively high capacity and energy density. When the median particle size of the second active material is too large, the mass content of the second doping element in the second active material is relatively low. When the gram capacity of the first active material 140 is relatively low, the gram capacity of the first material layer 112 is too low, thereby reducing the capacity of the positive electrode sheet 110, and then the capacity and energy density of the battery 200 are too low, thereby reducing the performance of the battery 200. When the median particle size of the second active material is too small, on the one hand, the difficulty of preparing the second active material is increased, thereby increasing the processing cost of the electrode assembly 100. On the other hand, correspondingly, the mass content of the second doping element in the second active material is too high, and excessive second doping elements may cause the second active material to produce heterophase compounds, thereby reducing the performance of the second active material in extracting and inserting lithium ions, and then reducing the capacity performance of the positive electrode sheet 110 and the electrode assembly 100, thereby reducing the capacity and energy density of the battery 200.

[0090] In some embodiments, the median particle size D3 of the third active material is in the range of 0.8 μm≤D3≤1.0 μm.

[0091] Specifically, the median particle size D3 of the third active material may be, but is not limited to, 0.8 μm, 0.82 μm, 0.83 μm, 0.85 μm, 0.88 μm, 0.9 μm, 0.92 μm, 0.93 μm, 0.95 μm, 0.96 μm, 0.97 μm, 0.99 μm, 1.0 μm, etc.

[0092] It can be understood that, in some embodiments, when the mass content of the second doping element in the second active material is higher, the median particle size of the first active material 140 is smaller.

[0093] In this embodiment, when the median particle size D3 of the third active material satisfies the range of 0.8 μm ≤ D3 ≤ 1.0 μm, the median particle size of the third active material is within a reasonable range. On the one hand, it is convenient to arrange the third active material in the second material layer 113, so that the second material layer 113 cooperates with the first material layer 112, so that the positive electrode plate 110 can not only slow down the lithium precipitation phenomenon on the surface of the negative electrode plate 130, but also has a higher capacity. On the other hand, the median particle size of the third active material is negatively correlated with the mass content of the third doping element. In other words, the mass content of the third doping element in the third active material is high and the mass content of the third doping element is also within a reasonable range. The bond energy of the Li-O bond in the third active material doped with the third doping element is weak, the diffusion resistance of lithium ions in the third active material is small, and the rate of the third active material to deintercalate lithium ions is fast, so that the third active material has a larger gram capacity, and the positive electrode plate 110 has a larger capacity. When the electrode assembly 100 is applied to a battery 200, the battery 200 has a higher capacity and energy density. When the median particle size of the third active material is too large, the mass content of the third doping element in the third active material is correspondingly low, thereby reducing the capacity of the positive electrode plate 110, and then the capacity and energy density of the battery 200 are too low, thereby reducing the performance of the battery 200. When the median particle size of the third active material is too small, on the one hand, the difficulty of preparing the third active material is increased, thereby increasing the processing cost of the electrode assembly 100. On the other hand, correspondingly, the mass content of the third doping element in the third active material is too high, and excessive third doping elements may cause the third active material to produce heterophase compounds, thereby reducing the performance of the third active material in extracting and inserting lithium ions, and then reducing the capacity performance of the positive electrode plate 110 and the electrode assembly 100, thereby reducing the capacity and energy density of the battery 200.

[0094] Please also see Figures 1 to 4 The present application also provides a battery 200 , which includes: the electrode assembly 100 provided in the present application and an electrolyte 210 , wherein the electrolyte 210 is used to wet at least a portion of the electrode assembly 100 .

[0095] In this embodiment, the electrode assembly 100 includes the positive electrode sheet 110 provided in the present application, and in the positive electrode sheet 110, the first sublayer 1121, the second sublayer 1122, the current collector layer 111 and the second material layer 113 are stacked in sequence and then wound, and the mass content of the first doping element in the first active substance 140 is less than the mass content of the second doping element in the second active substance, and the mass content of the first doping element in the first active substance 140 is less than the mass content of the third doping element in the third active substance, so that the gram capacity of the first active substance 140 is less than the gram capacity of the second active substance, and the gram capacity of the first active substance 140 is less than the gram capacity of the third active substance. Gram capacity: in the same turn of the winding structure, the first sublayer 1121 is closer to the central axis 101 than the second sublayer 1122 and the second material layer 113, and the gram capacity of the first active substance 140 is smaller than the gram capacity of the second active substance, which can balance the gram capacity per unit area at the corresponding positions of the first sublayer 1121 and the second sublayer 1122; the gram capacity of the first active substance 140 is smaller than the gram capacity of the third active substance, which can balance the gram capacity per unit area at the corresponding positions of the first material layer 112 and the second material layer 113, so as to avoid excessive lithium ions being extracted from the first sublayer 1121 and precipitated on the surface of the adjacent negative electrode sheet 130, thereby slowing down the lithium deposition on the surface of the negative electrode sheet 130. In addition, the second sublayer 1122 still has a relatively high gram capacity, so that the first material layer 112 still has a relatively high capacity, so that the positive electrode plate 110 still has a relatively high gram capacity, and ultimately the battery 200 has both higher energy and better safety performance, so that the battery 200 has a longer service life.

[0096] Optionally, the battery 200 further includes a shell 220 , wherein the shell 220 has a receiving cavity 221 for receiving the electrode assembly 100 and the electrolyte 210 .

[0097] The technical solution of this application is further introduced in the following with multiple embodiments:

[0098] Example 1 to Example 13, Comparative Example 1 and Comparative Example 2:

[0099] 1. Preparation of positive electrode sheet 110:

[0100] (1) Preparation of the first active material 140:

[0101] ① Weigh the iron source, phosphorus source, lithium source, carbon source, titanium source, etc., and then weigh an appropriate amount of inorganic oxide source (10% of the total amount of iron source, phosphorus source, lithium source, carbon source, and titanium source), mix them evenly on a ball mill, add an appropriate amount of pure water as a dispersant, and then perform high-energy ball milling (ball-to-material ratio of 5:2, speed of 2000r / min, time of 15h), and ball mill the raw materials into particles of appropriate size; the iron source is ferrous oxalate or ferrous phosphate or ferric oxide; the phosphorus source is lithium dihydrogen phosphate or ammonium dihydrogen phosphate; the lithium source is lithium carbonate or lithium hydroxide; the carbon source is glucose or sucrose or citric acid; the titanium source is titanium dioxide; the protective layer 142 of Examples 1 to 12 is an aluminum oxide layer, the source is aluminum hydroxide; the protective layer 142 of Example 13 is a calcium oxide layer, the source is calcium hydroxide. Among them, the first active material 140 used in Comparative Example 2 does not include a protective layer 142.

[0102] ② The ball-milled material was spray-dried (the pump speed was 10 mL / min and the drying temperature was set to 200°C) to form a powder with a certain particle size;

[0103] ③ The dried powder is placed in a vacuum atmosphere sintering furnace for high temperature calcination (protective atmosphere is nitrogen, 700°C, 15h), and then crushed by ball milling to obtain the first active material 140 of Examples 1 to 13, Comparative Examples 1 and 2, wherein the first active material 140 is a core-shell structure, the first active material 140 includes a core 141 and a protective layer 142, the protective layer 142 is coated on the periphery of the core 141, and the chemical formula of the core 141 of the first active material 140 is LiFe (1-x) M1 x PO4 / C, wherein M1 is a first doping element and the first doping element is selected from at least one of titanium, vanadium, magnesium or niobium, and the range of x is: 0.01≤x≤0.03.

[0104] ④ The particle morphology of the first active material 140 is obtained by electron scanning microscopy, such as Figure 5 The particle size distribution diagram of the median particle size of the first active material 140 is obtained by a laser diffraction particle size distribution measuring instrument (Malvern Mastersizer 3000), and the test standard used is the particle size distribution laser diffraction method GB / T19077-2016, so as to test the median particle size D1 of the first active material 140.

[0105] In the first active material 140 of Examples 1 to 13, Comparative Examples 1 and 2, the value of x, the type of M1 and the value of D1 are as shown in Table 1.

[0106] (2) Preparation of the second active substance and the third active substance:

[0107] ① Weigh an iron source, a phosphorus source, a lithium source, a carbon source, a titanium source, etc., mix them evenly on a ball mill, add an appropriate amount of pure water as a dispersant, and then perform high-energy ball milling (ball-to-material ratio of 5:2, rotation speed of 2000r / min, time of 15h) to ball-mill the raw materials into particles of appropriate size; the iron source is ferrous oxalate or ferrous phosphate or ferric oxide; the phosphorus source is lithium dihydrogen phosphate or ammonium dihydrogen phosphate; the lithium source is lithium carbonate or lithium hydroxide; the carbon source is glucose or sucrose or citric acid; the titanium source is titanium dioxide.

[0108] ② The ball-milled material was spray-dried (the pump speed was 10 mL / min and the drying temperature was set to 200°C) to form a powder with a certain particle size;

[0109] ③ The dried powder was placed in a vacuum atmosphere sintering furnace for high temperature calcination (protective atmosphere is nitrogen, 700°C, 15h), and then crushed by ball milling to obtain the second active material of Examples 1 to 13, Comparative Examples 1 and 2 and the third active material of Examples 1 to 13, Comparative Examples 1 and 2. The chemical formula of the second active material is LiFe (1-y) M2 y PO4 / C, wherein M2 is a second doping element and the second doping element is selected from at least one of titanium, vanadium, magnesium or niobium, and the range of y is: 0.04≤y≤0.06; the chemical formula of the third active material is LiFe (1-z) M3 z PO4 / C, wherein M3 is a third doping element and the third doping element is selected from at least one of titanium, vanadium, magnesium or niobium, and the range of z is: 0.04≤z≤0.06.

[0110] ④ Obtain the particle morphology of the second active substance or the third active substance by electron scanning microscopy, such as Figure 6 The particle size distribution diagram of the median particle size of the first active material 140 is obtained by a laser diffraction particle size distribution measuring instrument (Malvern Mastersizer 3000), and the test standard adopted is the particle size distribution laser diffraction method GB / T19077-2016, so as to test the median particle size D2 of the second active material and / or the median particle size D3 of the third active material.

[0111] It can be understood that in the above embodiments, the second active material and the third active material are formed by the same preparation process, that is, the composition parameters and structural parameters of the second active material and the third active material are the same. Figure 6The embodiment can characterize both the electron scanning microscope spectrum of the second active material and the electron scanning microscope spectrum of the third active material.

[0112] Understandably, by Figure 5 and Figure 6 It can be seen that Figure 5 The median particle size of the first active material 140 is larger than Figure 6 The median particle size of the second active material shown, and / or Figure 5 The median particle size of the first active material 140 is larger than Figure 6 The median particle size of the third active material is shown.

[0113] Among them, in the second active material of Examples 1 to 13, Comparative Examples 1 and 2, the value of y, the type of M2 and the value of D2 are shown in Table 1; in the third active material of Examples 1 to 13, Comparative Examples 1 and 2, the value of z, the type of M3 and the value of D3 are shown in Table 1.

[0114] (3) Preparation of positive electrode sheets 110 of Examples 1 to 13 and Comparative Example 2:

[0115] ① Set the second material layer 113 on the surface of the current collector layer 111: weigh the corresponding amount of the third active material, conductive carbon black, and polyvinylidene fluoride in a mass ratio of 95%:2%:3% in a stirring tank, and then add an appropriate amount of N-methylpyrrolidone (NMP) and stir for 6 hours to obtain a uniform slurry with suitable viscosity; apply the slurry evenly on the current collector layer 111 (aluminum foil) on the specified side by extrusion coating to form the second material layer 113, and the thickness of the second material layer 113 is d3.

[0116] ② Set the second sublayer 1122 on the surface of the current collector layer 111 away from the second material layer 113: weigh the corresponding amount of the second active substance, conductive carbon black, and polyvinylidene fluoride in a stirring tank in a mass ratio of 95%:2%:3%, and then add an appropriate amount of N-methylpyrrolidone (NMP) and stir for 6 hours to obtain a uniform slurry with suitable viscosity; apply the slurry evenly on the surface of the current collector layer 111 away from the second material layer 113 by extrusion coating to form a second sublayer 1122, and the thickness of the second sublayer 1122 is d2.

[0117] ③ The first sublayer 1121 is arranged on the surface of the second sublayer 1122 away from the current collector layer 111: the corresponding amount of the first active material 140, conductive carbon black, and polyvinylidene fluoride are weighed in a stirring tank according to a mass ratio of 95%: 2%: 3%, and then an appropriate amount of N-methylpyrrolidone (NMP) is added and stirred for 6 hours to obtain a uniform slurry with suitable viscosity; the slurry is uniformly coated on the surface of the second sublayer 1122 away from the current collector layer 111 by extrusion coating to form the first sublayer 1121, and the thickness of the first sublayer 1121 is d1. Among them, the thickness d1 of the first sublayer 1121, the thickness d2 of the second sublayer 1122, and the thickness d3 of the second material layer 113 satisfy: d3 = d1 + d2.

[0118] Through the above steps, the positive electrode sheets 110 of Examples 1 to 13 and Comparative Example 2 are obtained, and in the positive electrode sheets 110 of Examples 1 to 13 and Comparative Example 2, the values ​​of the thickness d1+d2 of the first material layer 112 are all 60 μm, and the thickness of the second material layer 113 is all 60 μm. The positive electrode sheet 110 includes a current collector layer 111, a first material layer 112, and a second material layer 113. The first material layer 112 is disposed on the side of the current collector layer 111 facing the central axis 101. The first material layer 112 includes a first sublayer 1121 and a second sublayer 1122. The first sublayer 1121 is closer to the central axis 101 than the second sublayer 1122. The second material layer 113 is disposed on the side of the current collector layer 111 away from the central axis 101.

[0119] Particularly, the first active material 140 used in Comparative Example 2 does not include the protective layer 142 .

[0120] Among them, in the positive electrode sheets 110 of Examples 1 to 13 and Comparative Example 2, the values ​​of the thickness d1 of the first sublayer 1121, the thickness d2 of the second sublayer 1122, and the thickness d3 of the second material layer 113 are as shown in Table 1.

[0121] (4) Preparation of the positive electrode sheet 110 of Comparative Example 1:

[0122] ① Set the second material layer 113 on the surface of the current collector layer 111: weigh the corresponding amount of the third active material, conductive carbon black, and polyvinylidene fluoride in a mass ratio of 95%:2%:3% in a stirring tank, and then add an appropriate amount of N-methylpyrrolidone (NMP) and stir for 6 hours to obtain a uniform slurry with suitable viscosity; apply the slurry evenly on the current collector layer 111 (aluminum foil) on the specified side by extrusion coating to form the second material layer 113, and the thickness of the second material layer 113 is d3.

[0123] ② Set the first material layer 112 on the surface of the current collector layer 111 away from the second material layer 113: weigh the corresponding amount of the second active substance, conductive carbon black, and polyvinylidene fluoride in a stirring tank in a mass ratio of 95%:2%:3%, and then add an appropriate amount of N-methylpyrrolidone (NMP) and stir for 6 hours to obtain a uniform slurry with suitable viscosity; apply the slurry evenly on the surface of the current collector layer 111 away from the second material layer 113 by extrusion coating to form the first material layer 112, and the thickness of the first material layer 112 is d1+d2.

[0124] Through the above steps, the positive electrode sheet 110 of comparative example 1 is obtained. In the positive electrode sheet 110 of comparative example 1, the thickness of the first material layer 112 and the thickness of the second material layer 113 are both 60 μm. The positive electrode sheet 110 includes a current collector layer 111, a first material layer 112 and a second material layer 113. The first material layer 112 is arranged on the side of the current collector layer 111 facing the central axis 101, and the second material layer 113 is arranged on the side of the current collector layer 111 away from the central axis 101. In other words, in the positive electrode sheet 110 of comparative example 1, the first material layer 112 is not divided into a first sublayer 1121 and a second sublayer 1122, and the first material layer 112 includes a second active material, and the mass content of the second doping element in the second active material is relatively high.

[0125] 2. Preparation of negative electrode sheet 130:

[0126] Corresponding amounts of artificial graphite, conductive carbon black and sodium carboxymethyl cellulose are weighed in a stirring tank at a mass ratio of 95%:2.5%:2.5%, and an appropriate amount of deionized water is added and stirred for 6 hours to obtain a uniform slurry with suitable viscosity; the slurry is then coated on a copper foil and placed in a vacuum oven, and dried at 150°C for 20 hours to obtain a negative electrode sheet 130.

[0127] 3. Preparation of the diaphragm 120:

[0128] The diaphragm 120 is a 16 um polyethylene film.

[0129] 4. Preparation of Battery 200:

[0130] (1) The positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are placed in a press for pressing, and then a sheet cutter is used to cut the positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 of a certain size respectively; the cut positive electrode sheet 110, the separator 120 and the negative electrode sheet 130 are stacked and arranged in sequence, and then wound to form an electrode assembly 100, wherein the electrode assembly 100 is a winding structure, and the winding structure has a central axis 101, wherein in the electrode assembly 100 of Examples 1 to 13, the first material layer 112 of the positive electrode sheet 110 is arranged at The current collector layer 111 faces the side of the central axis 101, the first sublayer 1121 is closer to the central axis 101 than the second sublayer 1122, and the second material layer 113 is arranged on the side of the current collector layer 111 away from the central axis 101; in the electrode assemblies 100 of Comparative Examples 1 and 2, the first material layer 112 of the positive electrode sheet 110 is arranged on the side of the current collector layer 111 facing the central axis 101, and the second material layer 113 is arranged on the side of the current collector layer 111 away from the central axis 101. Then, the positive and negative tabs are welded, and after drying, they are packaged with aluminum-plastic film to form the electrode assemblies 100 of Examples 1 to 13, Comparative Examples 1 and 2.

[0131] A solution obtained by dissolving 1 mol / L lithium hexafluorophosphate in a mixed solvent of ethylene carbonate and diethyl carbonate in a molar ratio of 1:1 was injected into the battery cell as the electrolyte 210, and finally packaged to form implementation batteries 1 to 13, comparative batteries 1 and comparative batteries 2.

[0132] Among them, the positive electrode plate 110 of Example 1 is applied to the electrode assembly 100 of Example 1 and assembled in the implementation battery 1, the positive electrode plate 110 of Example 2 is applied to the electrode assembly 100 of Example 2 and assembled in the implementation battery 2, the positive electrode plate 110 of comparative example 1 is applied to the electrode assembly 100 of comparative example 1 and assembled in comparative battery 1, and so on.

[0133] Table 1 below shows the composition parameters and structural parameters of the positive electrode sheet 110 of Examples 1 to 13, Comparative Examples 1 and 2.

[0134] Table 1: Composition parameters and structural parameters of the positive electrode sheet 110 of Examples 1 to 13, Comparative Examples 1 and 2.

[0135]

[0136]

[0137] The difference between Example 1 and Example 13 is that the protective layer 142 of Example 1 is an aluminum oxide layer, which is derived from aluminum hydroxide; and the protective layer 142 of Example 13 is a calcium oxide layer, which is derived from calcium hydroxide.

[0138] Performance test of battery 200:

[0139] 1. Rate discharge capacity test of implementation battery 1 to implementation battery 13, comparison battery 1 and comparison battery 2:

[0140] At 25° C., implementation batteries 1 to 13, comparative battery 1 and comparative battery 2 were respectively charged to 3.65 V at a 0.5 C rate, and then discharged to 2.5 V at a 0.5 C rate. After the discharge was completed, the 0.5 C discharge capacity was recorded.

[0141] The values ​​of 0.5C discharge capacity of implementation battery 1 to implementation battery 13, comparison battery 1 and comparison battery 2 are shown in Table 2.

[0142] 2. Test of interface lithium deposition of implementation battery 1 to implementation battery 13, comparison battery 1 and comparison battery 2:

[0143] At 25°C, implementation batteries 1 to 13, comparison battery 1 and comparison battery 2 were respectively charged to 3.65V at a rate of 1C, discharged to 2.5V at a rate of 1C, and then charged to 3.65V at a rate of 1C. Then, battery 200 was disassembled to observe the lithium deposition at the interface of the negative electrode plate 130.

[0144] Among them, the interface lithium deposition conditions of implementation batteries 1 to implementation batteries 13, comparative batteries 1 and comparative batteries 2 are shown in Table 2.

[0145] Table 2 below shows the performance parameters of implementation batteries 1 to 13, comparative battery 1 and comparative battery 2.

[0146] Table 2: Performance parameters of implementation batteries 1 to 13, comparative battery 1 and comparative battery 2.

[0147]

[0148]

[0149] Please refer to Table 1 and Table 2. From the data of Example 1 and Comparative Example 1, it can be seen that the positive electrode plate 110 of Example 1 includes a current collector layer 111, a first material layer 112 and a second material layer 113. The first material layer 112 includes a first sublayer 1121 and a second sublayer 1122, and the doping content of the first doping element of the first active material 140 in the first sublayer 1121 is less than the doping content of the second doping element of the second active material in the second sublayer 1122. In addition, the doping content of the first doping element of the first active material 140 is also less than the doping content of the third doping element of the third active material in the second material layer 113. The positive electrode plate 110 in Comparative Example 1 includes a current collector layer 111, a first material layer 112 and a second material layer 113. The first material layer 112 does not divide the first sublayer 1121 and the second sublayer 1122, but is directly composed of the second active material. This makes the 0.5C discharge capacity of the embodiment battery 1 slightly lower than that of the comparative battery 1. 0.5C discharge capacity, but the implementation battery 1 does not have lithium plating, while the comparison battery 1 has lithium plating. This is because: in Example 1, the doping content of the first doping element of the first active material 140 of the first sublayer 1121 is relatively low, the gram capacity of the first active material 140 is relatively low, and the gram capacity of the second active material and the third active material is relatively high. In the same circle of the winding structure, the first sublayer 1121 is closer to the central axis 101 than the second sublayer 1122 and the second material layer 113. The gram capacity of the first active material 140 is smaller than the gram capacity of the second active material, which can balance the gram capacity per unit area at the corresponding positions of the first sublayer 1121 and the second sublayer 1122, so as to avoid the first sublayer 1121 from extracting too many lithium ions and precipitating them on the surface of the adjacent negative electrode sheet 130, thereby slowing down the lithium plating on the surface of the negative electrode sheet 130, and making the service life of the implementation battery 1 longer than that of the comparison battery 1.

[0150] It can be seen from the data of Example 1 and Comparative Example 2 that, under the same other conditions, the first active material 140 used in Comparative Example 2 does not include a protective layer 142, which causes lithium deposition at the interface of the comparative battery 2. This is because: the first active material 140 of the battery 1 has a protective layer 142, and the protective layer 142 increases the impedance of lithium ions entering and exiting the inner core 141, thereby increasing the difficulty of the first active material 140 to deintercalate lithium ions, reducing the performance of the first active material 140 to deintercalate lithium ions, thereby further reducing the gram capacity of the first active material 140. In the same circle of the winding structure, the gram capacity per unit area of ​​the first sublayer 1121 can be reduced to balance the gram capacity per unit area at the corresponding positions of the first sublayer 1121 and the second sublayer 1122 and / or the second material layer 113, thereby avoiding the first sublayer 1121 from deintercalating too many lithium ions, so as to slow down the phenomenon of lithium deposition on the surface of the negative electrode plate 130 and extend the service life of the battery 200. This shows that by setting the protective layer 142 and setting the mass content of the first doping element to be relatively low, the two can play a synergistic role, so that there is a difference in the lithium ion diffusion capacity between the side of the positive electrode plate 110 close to the central axis 101 and the side away from the central axis 101, that is, the lithium ion diffusion capacity of the side of the positive electrode plate 110 close to the central axis 101 is worse than the lithium ion diffusion capacity of the side of the positive electrode plate 110 away from the central axis 101, so as to better slow down the occurrence of lithium precipitation.

[0151] It can be seen from the data of Examples 1 to 3 that, when other conditions are the same, the value of the doping content y of the second doping element in the second active material of Examples 1 and 2 satisfies the range of 0.04≤y≤0.06, and the value of the doping content z of the third doping element in the third active material satisfies the range of 0.04≤z≤0.06, but the value of y and the value of z in Implementation Battery 3 are both relatively large. Although Implementation Battery 1 to Implementation Battery 3 all show no lithium precipitation, the discharge capacity of Implementation Battery 3 at 0.5C is significantly smaller than the discharge capacity of Implementation Battery 1 and Implementation Battery at 0.5C. This is because: within a certain range, as the value of y gradually increases, it is beneficial to increase the capacity of the second sublayer 1122, and as the value of z gradually increases, it is beneficial to increase the capacity of the second material layer 113, so that the positive electrode plate 110 has a higher capacity, that is, Implementation Battery 1 and Implementation Battery 2 have a higher capacity. However, when the value of y is too large or the value of z is too large, the distortion of the crystal structure reaches a certain limit, and in the second active material, excessive second doping elements may cause the second active material to produce heterophase compounds, thereby reducing the performance of the second active material in extracting and inserting lithium ions. Similarly, in the third active material, excessive third doping elements may cause the third active material to produce heterophase compounds, thereby reducing the performance of the third active material in extracting and inserting lithium ions, and ultimately making the capacity of the implementation battery 3 lower than the capacity of the implementation battery 1 and the implementation battery 2. Therefore, preferably, the range of the value of y is: 0.04≤y≤0.05, and the range of the value of z is: 0.04≤z≤0.05.

[0152] From the data of Example 1, Example 4 and Example 5, it can be seen that when other conditions are the same, the mass content x of the first doping element in the first active material 140 of Example 1, Example 4 and Example 5 all satisfy the range of 0.01≤x≤0.03, so that the implementation battery 1, the implementation battery 4 and the implementation battery 5 all show no lithium precipitation phenomenon, and as the mass content of the first doping element gradually increases, the corresponding battery 200 also gradually increases at 0.5C discharge capacity. Correspondingly, the 0.5C discharge capacity of the implementation battery 5 is significantly lower than the 0.5C discharge capacity of the implementation battery 1 and the implementation battery 4. This shows that the increase in the mass content of the first doping element is also conducive to the increase in the capacity of the positive electrode plate 110. Therefore, it is necessary to regulate the value of the doping amount x of the first doping element so that the positive electrode plate 110 can have both a good capacity and slow down the occurrence of lithium precipitation, so that the corresponding battery 200 has both a high capacity and good safety performance. Therefore, preferably, the value of x is in the range of: 0.02≤x≤0.03.

[0153] It can be seen from the data of Examples 1, 6 to 9 that when the thickness d1 of the first sublayer 1121 and the thickness d2 of the second sublayer 1122 are constant values, as the thickness d1 of the first sublayer 1121 gradually increases, the value of d1 / d2 also increases. Although the battery 1, the battery 6 to the battery 9 can all show the phenomenon of no lithium precipitation, the 0.5C discharge capacity of the battery 1, the battery 6 to the battery 9 gradually decreases, which is not conducive to the improvement of the overall performance of the battery 200. Therefore, preferably, the value of d1 / d2 satisfies the range of 0.1≤d1 / d2≤0.5.

[0154] It can be seen from the data of Example 1 and Example 10 to Example 13 that, on the first aspect, the first doping element in Example 1 is Ti, the first doping element in Example 10 is V, the first doping element in Example 11 is Mg, and the first doping element in Example 12 is Nb. Implementation Battery 1, Implementation Battery 10 to Implementation Battery 12 all have a relatively high 0.5C discharge capacity, and no lithium precipitation occurs at the interface. This indicates that when the first doping element is selected from at least one of titanium, vanadium, magnesium or niobium, the first sublayer 1121 can play a role in slowing down the occurrence of lithium precipitation, so that the corresponding battery 200 has better applicability and a longer service life. Secondly, the protective layer 142 in Example 1 is an aluminum oxide layer, and the protective layer 142 in Example 13 is a calcium oxide layer. Both the implementation battery 1 and the implementation battery 13 have a higher 0.5C discharge capacity, and lithium deposition does not occur at the interface. This means that when a protective layer 142 is provided and the protective layer 142 is selected from an inorganic metal oxide layer, such as an aluminum oxide layer or a calcium oxide layer, the first sublayer 1121 can play a role in slowing down the occurrence of lithium deposition, so that the corresponding battery 200 has better applicability and a longer service life.

[0155] See also Figure 7 and Figure 8 The present application also provides an electrical device 300 , which includes: a device body 310 and a battery 200 provided in the present application, and the battery 200 supplies power to the device body 310 .

[0156] It can be understood that the battery 200 is electrically connected to the device body 310 .

[0157] In this embodiment, the battery 200 has both high energy and good safety performance, and the battery 200 has a long service life. When the battery 200 is applied to the power-consuming device 300, the battery 200 can provide stable power for the device body 310, which is conducive to improving the user experience.

[0158] Optionally, the power-consuming device 300 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Figure 7 The electrical equipment 300 of the embodiment is an energy storage battery cabinet.

[0159] It can be understood that the electric device 300 described in this embodiment is merely a form of the electric device 300 used by the battery 200, and should not be understood as a limitation on the electric device 300 provided in this application, nor should it be understood as a limitation on the electric device 300 provided in each embodiment of this application.

[0160] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.

[0161] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.

Claims

1. An electrode assembly, characterized in that: The electrode assembly is in a winding structure, the winding structure has a central axis, the electrode assembly includes the positive electrode sheet, a separator and a negative electrode sheet, the separator is located between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet includes: a current collector layer; a first material layer, the first material layer is disposed on a side of the current collector layer facing the central axis, the first material layer includes a first sublayer and a second sublayer, the first sublayer is closer to the central axis than the second sublayer, the first sublayer includes a first active material, the first active material is a core-shell structure, the first active material includes a core and a protective layer, the protective layer is coated on the periphery of the core, the core includes lithium iron phosphate and a first doping element, the second sublayer includes a second active material, the second active material includes lithium iron phosphate and a second doping element, and the mass content of the first doping element in the first active material is less than the mass content of the second doping element in the second active material; and A second material layer, the second material layer is arranged on a side of the current collector layer away from the central axis, the second material layer includes the third active substance, the third active substance includes lithium iron phosphate and a third doping element, and the mass content of the first doping element in the first active substance is less than the mass content of the third doping element in the third active substance.

2. The electrode assembly according to claim 1, characterized in that: The chemical formula of the core of the first active material is LiFe (1-x) M1 x PO4 / C, the chemical formula of the second active material is LiFe (1-y) M2 y PO4 / C, the chemical formula of the third active material is LiFe (1-z) M3 z PO4 / C, wherein M1 is a first doping element, the first doping element is selected from at least one of titanium, vanadium, magnesium or niobium, M2 is a second doping element, the second doping element is selected from at least one of titanium, vanadium, magnesium or niobium, M3 is a third doping element, the third doping element is selected from at least one of titanium, vanadium, magnesium or niobium, and satisfies the relationship: x<y, x<z.

3. The electrode assembly according to claim 2, characterized in that: In the first active material, the range of x is: 0.01≤x≤0.03; in the second active material, the range of y is: 0.04≤y≤0.

06.

4. The electrode assembly according to claim 3, characterized in that: In the third active material, the range of z is: 0.04≤z≤0.

06.

5. The electrode assembly according to claim 1, characterized in that: The thickness of the first sub-layer is d1, and the thickness of the second sub-layer is d2, and the relationship is satisfied: 0.1≤d1 / d2≤0.

5.

6. The electrode assembly according to claim 5, characterized in that: The thickness of the second material layer is d3, which satisfies the relationship: 0.85≤(d1+d2) / d3≤1.

7. The electrode assembly according to claim 1, characterized in that: The median particle size D1 of the first active material is in the range of 1.1 μm ≤ D1 ≤ 1.3 μm, the median particle size D2 of the second active material is in the range of 0.8 μm ≤ D2 ≤ 1.0 μm, and the median particle size D3 of the third active material is in the range of 0.8 μm ≤ D3 ≤ 1.0 μm.

8. The electrode assembly according to any one of claims 1 to 7, characterized in that: The protective layer is an inorganic metal oxide layer, and the protective layer is selected from at least one of an aluminum oxide layer, a calcium oxide layer, and a titanium oxide layer.

9. A battery, characterized in that: The battery comprises: The electrode assembly according to any one of claims 1 to 8; and An electrolyte is used to wet at least a portion of the electrode assembly.

10. An electrical device, characterized in that: The electrical equipment includes: The device itself; and The battery of claim 9, wherein the battery is used to power the device body.

Citation Information

Patent Citations

  • Winding type battery cell and lithium ion battery

    CN113571777A

  • Electrochemical device and electric device

    CN116072817A

  • Positive plate, lithium ion battery and energy storage equipment

    CN116470005A